The challenge of epistemic access and the intention of the error verb in the moral practitioner (Based on the views of Bentham, Kant and Martyr Sadr) - Behruz Muhammadimunfared; Hasan Lahootiyan (اخلاق وحیانی, 2021)
This study seeks to investigate the moral practice and the place of consciousness and knowledge in the realization of moral behavior based on the two general approaches of Kantian moral conscientiousness and Bentham pragmatic utilitarianism as well as the approach of Martyr Sadr. The main challenge is what effect do the two elements of consciousness and will (intention) have on the morality or non-morality of an action? And in the case of moral experience, if our awareness of the correctness or incorrectness of an action is wrong, and we will the wrong action, which is in fact true, what role do this awareness and will play in the content of that action; Do we consider that verb right or wrong?To address such a challenge, Section 1 addresses the issue of epistemic access and knowledge of the justification of normative propositions. In Part 2, he states that by accepting Bentham's pragmatic utilitarianism, even under the premise of moral realization, rebellion and rebellion have not taken place, and that the doer of the act does not deserve to be condemned. Section 3 also states that, on the basis of Kant's moral conscientiousness, a kind of rebellion has certainly taken place with moral practice, and that the behavior of the practitioner is immoral, and that person deserves condemnation. In Part 4, Martyr Sadr's approach to the executor is examined and compared with Kant and Bentham.